Synthesis and luminescent properties of aluminium oxide-titanium dioxide nanocomposites doped with different rare-earths ions - Mokoena, Teboho Patrick (University of the Free State, 2016)
Alumina-titania (Al2O3-TiO2) is one of the most useful nano-composites to host up-conversion rare-earth (UCRE) ions to prepare light emitting nano-materials or nano-phosphors. These nano-composites have received a special attention because of their excellent thermal, chemical and mechanical stability. Alumina (Al2O3) is a ceramic material with high level of strength, toughness and tribological properties. Titania (TiO2) is a wide bandgap semiconductor material that is used in different application including photocatalytic activities, solar cells, hydrogen storage and sensors. The singly doped α- Al2O3:Yb3+ phosphor powder was successfully synthesized by solution combustion method. The structure of the phosphor powders was characterized with powder X-ray diffractometer (XRD). The XRD patterns confirmed that the phosphors crystallized in the hexagonal phases of α-Al2O3 with space group R3c and the average crystallite size was 29 nm estimated from Debye-Scherrer equation. The Fourier transform infrared (FTIR) measurements confirmed the characteristic bonds of Al-O from α-Al2O3. The particle morphology and elemental composition of the phosphors were characterized by field emission scanning electron microscope (FE-SEM) coupled with an energy dispersive x-ray spectroscopy (EDS). The phosphor powders were excited in ultraviolet (UV) region with excitation wavelength of 325 nm and the corresponding near infrared (NIR) emission was observed at 975 nm. The NIR emission was assigned to 2F5/2→2F7/2 transition of Yb3+. The bluish green emission with maxima at ~ 480 nm was observed as a result of cooperative luminescence of Yb3+ when the powders were excited in the NIR with excitation wavelength of 980 nm. The TiO2:Er3+ nano-phosphor powder were successfully synthesized by sol-gel method at room temperature XRD confirmed that nano-phosphor has crystallized in the tetragonal phases of anatase and rutile with space groups of (see PDF full text) and (see PDF full text) , respectively. An average crystallite size of the undoped TiO2 was 26 nm. The FE-SEM confirmed nano-rods particle morphology with diameter and length of 78 ± 36 nm and 1.51 ± 0.30 μm, respectively. The FTIR revealed the characteristic bonds of Ti-O due to the presence of TiO6 in titania. The nano-phosphor powders were excited in the NIR region with excitation wavelength of 980 nm and the corresponding visible emissions were observed at 527, 564 and 665 nm. The green emission with maxima at 527 and 564 nm were assigned to (2H11/2, 4S3/2)→4I15/2 while red emission at 665 nm was assigned to 4F9/2→4I15/2 transition of Er3+ ion. The excited state absorption (ESA) mechanism of up-conversion (UC) process was discussed extensively. The nano-composites of Al2O3-TiO2:Yb3+,Er3+ and Al2O3-TiO2:Yb3+,Tm3+ phosphor powders were successfully synthesized by sol-gel method. XRD patterns confirmed the mixed oxides of titania (TiO2) rutile phase and an early crystallization of alumina (α-Al2O3) phase. The XRD patterns were consistent with JCPDS card no. 46-1212 and 21-1272 for α-Al2O3 and TiO2 rutile phases, respectively. An average crystallite size of ~ 36 nm was estimated from Debye-Scherrer equation. FE-SEM confirmed nano-rods morphology self-assembled with spherical particles. In Yb3+-Er3+ codoped nano-composites; the powders were excited in the NIR region with excitation wavelength of 980 nm and corresponding visible emissions were observed at 523, 548 and 658 nm. The green emission with maxima at 523 and 548 nm were assigned to (2H11/2, 4S3/2)→4I15/2 while red emission at 658 nm was assigned to 4F9/2→4I15/2 transition of Er3+ ion. In Yb3+-Tm3+ codoped nano-composites; the powders were excited in NIR region with excitation wavelength of 980 nm and corresponding visible to NIR emissions were observed at 480, 650, 693 and 800 nm. The blue emission with maxima at 480 nm was assigned to 1G4→3H6, red emission with maxima at 650 and 693 nm were assigned to 1G4→3F4 and 3F3→3H6 and NIR emission with maxima at 800 nm was attributed to 3H4→3H6 transitions of Tm3+ ion. The other optical properties were investigated with the characterization techniques such as FTIR and UV-vis.
Dissertation (M.Sc. (Physics))--University of the Free State, 2016
Keywords: Alumina; Titania; Nano-composites; Nano-phosphor; Up-conversion; Red; Green; Blue; Near-infrared; Emission